Development of Surgical Tools and Procedures for Experimental Preclinical Surgery Using Computer Simulations And 3D Printing - Barcik, Jan; Ernst, Manuela; Schwyn, Ronald; Freitag, Linda; Dlaska, Constantin Edmond; Drenchev, Ludmil; Todorov, Stoil; Skulev, Hristo; Epari, Devakara R.; Zeiter, Stephan; et al. (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Abstract—Experimental preclinical surgeries require high accuracy and repeatability in all applied procedures. For in vivo studies investigating bone fracture healing it is crucial to create precisely and consistently the experimental bone fractures in all included subjects. In large animal models the required precision is usually achieved by application of dedicated drilling jigs and cutting guides that often need to be individually designed in order to fulfil the requirements of a particular experiment. Moreover, their final design may considerably differ from the prototypes. Hence, the designing and testing processes require multiple iterative refinement loops substantially increasing the costs of the experiment. Therefore, a framework for development of tailor-made instruments for experimental preclinical surgeries is established to reduce the investment of time and financial effort.